Inas Halabi’s We No Longer Prefer Mountains (2022). Creating an Artistic Counternarrative within the Druze Community in Israel/Palestine through Oral History and Fukeiron Methodologies (Cinéma & Cie. Film and Media Studies Journal, 2024)
The article looks at the research methods that lie behind the film We No Longer Prefer Mountains (2022) by Palestinian artist Inas Halabi. The movie represents a counternarrative of the identity and political issues of the Druze community living in Israel, achieved from within through an immersive glimpse. The aim is to analyse the way the visual artist relies on specific methodologies (which are contextualized within the field of Palestinian studies) to build an alternative perspective on Druze history. On one side, the paper considers oral history as it is practiced in the film: a method to write history from below, to highlight the interconnections of individual and collective stories, and to exhibit forms of sumud (resistance) in everyday life. On the other, it focuses on fukeiron, a method of filming the landscape applied by Halabi to expose symbols of colonial control hidden in both natural and urban environments. Overall, the article thinks about the role that the artist can play and the way she can contribute to a militant and decolonial research from her particular position and application of specific methodologies.
Keywords: Counterhegemonic; Narrative; Druze; Oral History; Fukeiron